Soft skills competencies of quantity surveying graduates in Malaysia: employers’ views and expectations - Shafiee, Hasbullah; Syed Khuzzan Alhabshi, Sh Mazlina; Mohyin, Nur Affah (Universiti Teknologi Malaysia, 2014)
Various organizations employ Quantity Surveying (QS) graduates. The diversity of employment opportunities bring the needs of QS graduates to equip with the key competencies to be able to work effectively and efficiently with other professionals. The QS profession faces threats to its traditional roles and functions as a result of changing client needs in the construction industry advances in technology and the particular needs of a developing economy. Within the context of the current situation, the globalization is pushing QS graduates to become competitive in term of soft skills that they possess such as communication skills, problem-solving skills, leadership, and teamwork. This research adopted a survey approach, using a questionnaire as the data collection technique. 80 questionnaires were distributed to employers, or human resource (HR) managers of the organizations that had QS graduates working with them. This paper reports on the views and expectations of the employers towards the soft skills of QS graduates in Malaysia. The employers were asked to rate their views towards current QS graduates’ soft skills’ performance in Malaysia as well as to assess their expectations of these graduates’ soft skills based on a five-point Likert scale. From the findings, a ‘competency gap’ between the current local university QS graduates’ soft skills’ performance and their expectations were identified, and discussed. This paper also presents the recommendations made by the employers towards Higher Education Institutions (HEIs) in Malaysia producing QS graduates in order to improve and prepare the graduates for their work place.